Chemical product design - Cussler, E. L.; Moggridge, G. D. (Cambridge : Cambridge University Press, 2011)
"The chemical industry is changing, going beyond commodity chemicals to a palette of higher value added products. This groundbreaking book, now revised and expanded, documents this change and shows how to meet the challenges implied. Presenting a four-step design process - needs, ideas, selection, manufacture - the authors supply readers with a simple design template that can be applied to a wide variety of products. Four new chapters on commodities, devices, molecules/drugs and microstructures show how this template can be applied to products including oxygen for emphysema patients, pharmaceuticals like taxol, dietary supplements like lutein, and beverages which are more satisfying. For different groups of products the authors supply both strategies for design and summaries of relevant science. Economic analysis is expanded, emphasizing the importance of speed-to-market, selling ideas to investors and an expectation of limited time in the market. Extra examples, homework problems and a solutions manual are available"--
Machine generated contents note: 1. An introduction to chemical product design; 2. Needs; 3. Ideas; 4. Selection; 5. Product manufacture; 6. Commodity products; 7. Devices; 8. Molecular products; 9. Microstructures; 10. A plan for the future.
Keywords: Chemical industry